PROBLEMATIKA FATWA MUI SEBAGAI PRODUK HUKUM ISLAM - Umar B; Gassing, Qadir; Kurniati (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
The Qur'an and hadith are the main sources of Islamic teachings. Both contain rules that serve as guidelines for thinking and behavior for Muslims. The rules contained in these two basic principles or sources are then popularly referred to as Islamic law. The ulama studied and explained it through their ijtihad, thus giving birth to formulations relating to legal issues called fiqh. The main problems of this research are 1) What is the Essence of Ulama Fatwa 2) How is the Ulama Fatwa Ijtihad Method 3) How is the Ulama Fatwa Enforced. This research is a type of library research, namely research whose object of study uses library data in the form of books as a data source. This research was carried out by reading, reviewing and analyzing various existing literature, in the form of the Qur'an, hadith, books , as well as research results. The results of this research are that a fatwa is a mufti's response or answer to requesting a fatwa or problems occurring in society related to legal issues. As for the approach usually used by a mufti in issuing or establishing a fatwa including: Nash qat'i approach, qauli approach, and approach Manhaji. However, if people in Indonesia do not obey the fatwa, there are no sanctions imposed on him because of a fatwa is not of the same status as the law.